A identidade cultural gaúcha: análise das produções acadêmcias e a realidade de um Centro de Tradição Gaúcha - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Brazilian culture and identity are plural and diversified, due to the processes of immigration and migration across the country's great geographic space, to the countless moments of socialization that took place in spaces marked by heterogeneities, as well as by the singularities of each individual. For this reason, the present study seeks to answer the following problem: how does the academic literature report the process of construction of the gaúcha cultural identity? Based on this perception, we sought to verify in locus whether what is presented in Brazilian literature effectively occurs in the daily life of a Gaúcha Tradition Center located outside Rio Grande do Sul. Thus, the general objective of the dissertation was to identify and analyze what the scientific literature produced in Brazil presents about the process of building a gaúcha cultural identity. For this, the dissertation was built from the Scandinavian method, which proposes in its structuring, the development of articles that have complementarity to understand the research problem. Through the state of knowledge in article 1, it is noted that none of the works found reports the use of the term “cultural identity”, and its relationship with gaucho culture is demonstrated through studies addressing an imaginary created around the figure of the gaucho . In addition, most studies are carried out in the southern region of the country, especially in Rio Grande do Sul, demonstrating the lack of studies with other perspectives of Rio Grande do Sul culture in other places of interaction and identification. With article 2, a constant use of the author Stuart Hall was identified in the studies, which presented repetitive definitions about cultural identity, thus evidencing the lack of in-depth discussions about this concept. Given this gap, an analysis of the concepts of culture and identity was carried out in Article 3. It is noteworthy that understanding these concepts has several approaches, it is to leave an isolated perspective of thought, in order to be rethought and then dialogued from new theoretical frameworks. Observing that the cultural identification process goes through an initial essence, the root of the culture, which can be perpetuated by the individual, or not. This opening new visions for the world and its culture in the identification processes. In view of the above, article 4 made it possible to verify that the processes of cultural identification in diasporic situations happen from a distance from the traditions experienced in the abandoned land, a link is formed with the culture to which it was previously inserted and that in the present is distant . It is observed that the gaucho in his experience at CTG, seeks to bring the aspects closer to the culture that was left, in which two cultures converge with his purposes: traditionalist and traditional, the latter more open to changes and acceptance of the inserted places, in which differentiation processes begin to influence culture making it more flexible and open to new habits and customs. Finally, it is noted that cultural identity is fully constructed and undergoes changes according to the experiences of individuals, in which each subject becomes responsible for making their traditions the construction of their own self. Reinforcing how the adaptation of the gauchos is present through the creation of the CTGs, in an attempt to not totally lose the gaucho culture.
Keywords: Identidade; cultura; identidade cultural; cultura gaúcha; Identity; culture; cultural identity; gaucho culture; CNPQ::CIENCIAS SOCIAIS APLICADAS